Breeding success, prey use, and mark-resight estimation of burrowing owls nesting on black-tailed prairie dog towns: plague affects a non-susceptible raptor - Conrey, Reesa Catheline Yale, author; Antolin, Michael F., advisor; Theobald, David M., committee member; Davis, Richard A., committee member; Savidge, Julie, committee member; Skagen, Susan K., committee member (Colorado State University. Libraries, 2010)
Introduced pathogens such as the bacterium (Yersinia pestis) that causes plague can have far-reaching effects on native ecosystems that go beyond the mortality of infected individuals. We investigated the effects of plague, prairie dog town dynamics, and rainfall on burrowing owls (Athene cunicularia) nesting in black-tailed prairie dog (Cynomys ludovicianus) burrows in the shortgrass steppe of northern Colorado. We examined effects on prey use, nest density, and breeding success, and used mark-resight methods for owl population estimation. Prairie dogs experience high mortality from plague, and their colonies are periodically extirpated by outbreaks. Plague does not make owls sick, but they may be affected as unmaintained burrows collapse, vegetation grows taller, and the anti-predator benefits of prairie dog association are lost. From 2005 - 2008, we monitored 322 nest attempts by 311 burrowing owl pairs on the Pawnee National Grassland and collected regurgitated pellets and prey remains. We banded owlets in 2007, and our first objective was to use a mark-resight protocol to estimate abundance, apparent survival, and temporary emigration. The Poisson-log normal mark-resight model (McClintock and White 2009) has recently been implemented in Program MARK (White and Burnham 1999). This model improves upon previous mark-resight models because individual identifications are not required 100% of the time, and individuals may die or be temporarily unobservable. Modeling showed that owlets in better condition that weighed more at first capture had higher survival throughout the summer and were more likely to be above ground. Our suggested improvements to field protocols should improve abundance estimation in the future. Our second objective was to examine the effects of precipitation, nest density, and plague on prey use and to determine whether prey composition influenced nest or fledging success. We quantified prey use and then analyzed diet composition using multi-response permutation procedures (MRPP) and indicator species analysis. Burrowing owls ate a huge variety of prey dominated by beetles, grasshoppers, ants, rodents, and songbirds. Insects comprised 95% of their diet by number, but only 11% by biomass. Owls in the driest year of our study and those at successful and very productive nests ate fewer birds and more mammals. Owl diet was unchanged by plague outbreaks, except that several bird species were less commonly eaten following epizootics. It appears that burrowing owls often forage outside of prairie dog towns, making town-level differences less relevant to owl diets. Our third objective was to determine the effects of plague, prairie dog town dynamics, and rainfall on nest fate, fledging success, and distances from each nest to its three nearest neighbors. Generalized linear modeling showed that rainfall was the strongest predictor of nest and fledging success, with higher rainfall associated with lower breeding success. Nests were more likely to succeed when plague events were more recent, and they produced more fledglings on towns where any extirpation was brief, and prairie dogs were otherwise resident on site for a longer time. Nests were closest together on recently plagued towns where prairie dog activity had been nearly continuous for a long time and recolonization was rapid. Although ubiquitous on active prairie dog towns, burrowing owls were nearly absent from towns that were not recolonized after plague epizootics. Both precipitation and plague influenced population dynamics of breeding burrowing owls. We found strong relationships among rainfall, prey species composition, and owl breeding success, and only half the owlets that emerged from burrows survived to fledge during the wettest July of our study. Precipitation regimes are expected to become more extreme in the future, which will likely have consequences for burrowing owls and other dryland species and may affect the size and frequency of plague outbreaks (Stapp et al. 2004). Although owls were absent from towns that were not recolonized after plague epizootics, it appears that burrowing owls can adapt to plague and even benefit in some cases. If conservation of burrowing owls is a primary goal, our results suggest that it will be more useful to preserve prairie dog habitat and connectivity between towns at a landscape scale than to intensively manage plague.
Department Head: N. LeRoy Poff.